Papel modulador do carvacrol sobre células progenitoras endoteliais - investigação de mecanismos regenerativo em nível molecular - Gonçalves, Tays Amanda Felisberto (2023)
Carvacrol is a phenolic monoterpene with diverse biological activities, highlighting its antioxidant and antihypertensive capacity. However, there is little evidence demonstrating its influence on vascular regeneration. The present study evaluated the possible modulation of carvacrol in endothelial repair induced by endothelial progenitor cells (EPC). For in vitro assays, EPC was isolated from the bone marrow of Wistar rats and cultured for seven days in an endothelial basal mediurn. The cultured cells were divided into four experimental groups: control (CTL), 1 µM angiotensin II (ANG), 0.1 µM carvacrol (CTL-CAR), and 1 µM angiotensin treated with 0.1 µM carvacrol (ANG-CAR). All substances were incubated for 24 hours to carry out the experimental protocols. Cytotoxicity was assessed using the MTT assay. The modulation profile of carvacrol on EPC was evaluated through the detection of reactive oxygen species (ROS) and nitric oxide (NO), cell adhesion and migration tests, and evaluation of the expression of endothelial nitric oxide synthase (eNOS), catalase (CAT), superoxide dismutase (SOD) and Nrf2. For the in vivo tests, the animals were divided into five groups: Wistar Kyoto normotensive control (WKY-CTL) and hypertensive control (SHR-CTL); and hypertensive patients treated with carvacrol 50 mg/kg (SHR-C50), carvacrol 100 mg/kg (SHR-C100) or resveratrol (SHR-RE10). All rats were treated intragastrically, once a day, for four weeks. The experimental protocols were approved by CEUA-UFPB n° 2171120320. Systolic blood pressure (SBP) was measured weekly from the tail cuff. EPC was isolated from bone marrow and peripheral circulation and quantified by flow cytometry. EPC functionality was assessed after cultivation by quantification of colony forming units (CFU), assessment of eNOS, intracellular detection of ROS, and assessment of senescence. The superior mesenteric artery was isolated to evaluate the quantification of ROS, CD34, and CD31. Treatment of the ANG-CAR group reduced oxidative stress and improved EPC adhesion and migration. Increased EPC performance involves increased expression of eNOS, with a consequent increase in NO production. Furthermore, an increase in the expression of SOD, CAT, and Nrf2 was observed in EPC treated with carvacrol. Carvacrol treatment induced EPC migration, increased CFU formation, eNOS expression and activity, and reduced ROS and senescence. Furthermore, carvacrol reduced vascular ROS and increased the expression of CD31 and CD34. This study showed that treatment with carvacrol improves EPC functionality, contributing to the reduction of endothelial dysfunction.